Low-resistance Ti/Au ohmic contacts to Al-doped ZnO layers - Kim, HK; Han, SH; Seong, TY; Choi, WK (AMER INST PHYSICS, 2000)
We report on low-resistance ohmic contacts to the moderately doped n-type ZnO:Al(n(d)=2x10(17) cm(-3)) obtained using Ti (30 nm)/Au (50 nm) metallization schemes. Annealed Ti/Au contacts exhibit linear current-voltage characteristics, showing that high-quality ohmic contacts are formed. The Ti/Au scheme produces a specific contact resistance of 2x10(-4) Omega cm(2) when annealed at 300 degrees C for 1 min in a N-2 atmosphere. (C) 2000 American Institute of Physics. [S0003-6951(00)00537-4].
Keywords: ELECTRICAL-PROPERTIES; FILMS